PENGARUH NCT DREAM SEBAGAI BRAND AMBASSADOR DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MIE INSTAN DENGAN KOREAN WAVE SEBAGAI VARIABEL INTERVENING - Tijun, Siti; Saino, Saino (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This study was conducted to determine the effect of NCT Dream as the Brand of Ambassador and Brand Image against the decision of the instant noodle purchase with korean wave as an intervening variable in Surabaya. This research uses descriptive quantitative. The population in this research is the consumer who once built a lemonilo noodle and who knows NCT Dream in Surabaya City. The sample used is 97 samples for this research with consumer criteria that has made purchases more than 2 times 17 years old to 35 years, using purposive sampling technique and using the Lemeshow formula. The data analysis technique used is simple linear regression analysis, multiple regression analysis, path analysis in this study using the IPM 25 SPSS version. The results of this study indicate that the variables of the Ambassador brand (X1) significantly influence the decision of purchase of the lemonilio noodles, the brand image (X2) variables significantly affect the purchase decision, the korean wave (Z) variable impact positive but not significant to the purchase decision, the variables of the Ambassador brand (X1) indirectly affected the purchase decision through korean wave, the Brand Image variable (X2) indirectly affected the purchase decision through korean wave and Variables Brand Ambassador (X2) and Brand Image (X2)) not equally to purchase the purchase decision through the korean wave Mediation (Z) as interventive mediation. Keywords: Brand Ambassador; Brand Image; Purchase Decision; Korean Wave